Evaluation of Methicillin-Resistant Staphylococcus aureus Carriage and High Livestock Production Areas in North Carolina through Active Case Finding at a Tertiary Care Hospital - Feingold, Beth J.; Augustino, Kerri L.; Curriero, Frank C.; Udani, Paras C.; Ramsey, Keith M. (My University, 2019)
: Recent reports from the Netherlands document the emergence of novel multilocus sequence typing (MLST) types (e.g., ST-398) of methicillin-resistant Staphylococcus aureus (MRSA) in livestock, particularly swine. In Eastern North Carolina (NC), one of the densest pig farming areas in the United States, as many as 14% of MRSA isolates from active case finding in our medical center have no matches in a repetitive sequence-based polymerase chain reaction (rep-PCR) library. The current study was designed to determine if these non-matched MRSA (NM-MRSA) were geographically associated with exposure to pig farming in Eastern NC. While residential proximity to farm waste lagoons lacked association with NM-MRSA in a logistic regression model, a spatial cluster was identified in the county with highest pig density. Using MLST, we found a heterogeneous distribution of strain types comprising the NM-MRSA isolates from the most pig dense regions, including ST-5 and ST-398. Our study raises the warning that patients in Eastern NC harbor livestock associated MRSA strains are not easily identifiable by rep-PCR. Future MRSA studies in livestock dense areas in the U.S. should investigate further the role of pig–human interactions.
Keywords: MRSA; MLST; rep-PCR; North Carolina; livestock; cluster detection